2018
DOI: 10.1186/s12903-018-0591-6
|View full text |Cite
|
Sign up to set email alerts
|

Predicting oral malodour based on the microbiota in saliva samples using a deep learning approach

Abstract: BackgroundOral malodour is mainly caused by volatile sulphur compounds produced by bacteria and bacterial interactions. It is difficult to predict the presence or absence of oral malodour based on the abundances of specific species and their combinations. This paper presents an effective way of deep learning approach to predicting the oral malodour from salivary microbiota.MethodsThe 16S rRNA genes from saliva samples of 90 subjects (45 had no or weak oral malodour, and 45 had marked oral malodour) were amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 18 publications
0
27
0
1
Order By: Relevance
“…In turn, the presence of bacteria, such as Firmicutes, Proteobacteria, Bacteroidetes, Actinobacteria, and Fusobacteria, was demonstrated in both the samples from examined and control groups. Firmicutes was the most abundant phylum in saliva samples from both groups [110,111].…”
Section: Chemical Compound Bacteriamentioning
confidence: 95%
“…In turn, the presence of bacteria, such as Firmicutes, Proteobacteria, Bacteroidetes, Actinobacteria, and Fusobacteria, was demonstrated in both the samples from examined and control groups. Firmicutes was the most abundant phylum in saliva samples from both groups [110,111].…”
Section: Chemical Compound Bacteriamentioning
confidence: 95%
“…In the prediction of oral odor, the model was constructed and predicted by using 108 significantly different bacteria found in saliva samples, which can reach 78.9% accuracy. Among those bacteria, it was found that Bacteroides, Prevotella and Porphyromonas had the most discriminatory validity on oral odor [38]. In the prediction of oral and oropharyngeal carcinoma, the AUC values predicted by seven biomarkers such as Rothia, Haemophilus and Capnocytophaga of oral microbiota could even reach 90%-100% [39].…”
Section: Discussionmentioning
confidence: 97%
“…The remaining 16 papers were fully examined. The high-level data from Table 1 [45] Dataset study Tenfold Genus Obesity [46] New methods Tenfold, 10 times Species 5 body sites 24 environments Colorectal cancer [47] New methods Tenfold Genus Classification of body site Classification of subjects Classification of disease states [48] Dataset study Tenfold Species Colorectal Cancer (CRC) and Colorectal Adenoma (CRA) [49] Dataset study NA Genus Crohn's Disease (CD) [50] Dataset study Tenfold, 10 times Species Colorectal Polyps [51] Dataset study Leave-one-out Species Colorectal Adenoma Colorectal Cancer [52] Dataset study Fivefold, 5 times Genus Type 2 diabetes (T2D) Liver Cirrhosis Rheumatoid Arthritis (RA) [53] Dataset study Leave-one-out Genus Oral malodour…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the work by Zhou and Gallins [17] is a review. Although it has been excluded from the study, it provided four new articles [48,52,53,85] to be added in full-text to the list of the eligible papers. Also, the paper [18] has been excluded as it is also a review.…”
Section: Selection Of Sources Of Evidencementioning
confidence: 99%